2019
DOI: 10.3762/bjoc.15.205
|View full text |Cite
|
Sign up to set email alerts
|

α-Photooxygenation of chiral aldehydes with singlet oxygen

Abstract: Organocatalytic α-oxygenation of chiral aldehydes with photochemically generated singlet oxygen allows synthesizing chiral 3-substituted 1,2-diols. Stereochemical results indicate that the reaction in the presence of diarylprolinol silyl ethers is highly diastereoselective and that the configuration of a newly created stereocenter at the α-position depends predominantly on the catalyst structure. The absolute configuration of chiral 1,2-diols has been unambiguously established based on electronic circular dich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Singlet oxygen has also been efficiently used for enantioselective and chemoselective oxidations of many organic compounds. Notably, the Gryko's group recently described an enantio-and diastereoselective approach involving a porphyrinbased photooxygenation of aldehydes with sequential reduction to yield chiral diols in yields up to 91% and significant er (up to 96:4), but low dr (up to 66:33) (Scheme 40) [90].…”
Section: Singlet Oxygen In Pericyclic Reactionsmentioning
confidence: 99%
“…Singlet oxygen has also been efficiently used for enantioselective and chemoselective oxidations of many organic compounds. Notably, the Gryko's group recently described an enantio-and diastereoselective approach involving a porphyrinbased photooxygenation of aldehydes with sequential reduction to yield chiral diols in yields up to 91% and significant er (up to 96:4), but low dr (up to 66:33) (Scheme 40) [90].…”
Section: Singlet Oxygen In Pericyclic Reactionsmentioning
confidence: 99%
“…However, the enantioselective transfer of 1 O 2 is still challenging, because of its short lifetime. Although the α-hydroxylation of aldehydes and ketones was realized by organocatalysis with moderate to good ee ( enantiomeric excess ) [ 14 , 15 , 16 ], ene reactions or cycloadditions proceed less successfully. Thus, asymmetrically modified zeolites [ 17 ], chiral salts [ 18 ], or chiral sensitizers [ 19 ] afforded only low stereoselectivities.…”
Section: Introductionmentioning
confidence: 99%
“…5 Unfortunately, the reactions showed only moderate enantioselectivity, and extensive efforts on further improvements have met with only very limited success over the past two decades. 6 The associated difficulties are multifaced. First, the stereocontrol with singlet oxygen is notoriously challenging due to the fleeting nature and small size of 1 O 2.…”
mentioning
confidence: 99%
“…Previous studies by Córdova have shown that aminocatalysis was viable to mediate aerobic hydroxylation of ketone and aldehyde by enamine-singlet oxygen coupling . Unfortunately, the reactions showed only moderate enantioselectivity, and extensive efforts on further improvements have met with only very limited success over the past two decades . The associated difficulties are multifaced.…”
mentioning
confidence: 99%